Implementasi Manajemen Pendidikan Karakter Dalam Mengembangkan Minat, Sikap Dan Perilaku Positif Siswa - Dian Anggreini; Umi Kulsum; Mujiyatun (Journal of Islamic Education and Learning, 2023)
Education management plays an important role in determining the direction of development of a nation. To achieve this, character education must be implemented in every world of a child's life, from the family to the school system. Cooperation between character education and educational curricula is needed to ensure that all children develop positive attitudes and behaviors. Therefore, this study aims to describe and understand education management in developing students' interests, attitudes and positive behavior at SMP Quran Darul Fattah Lampung Selatan. This qualitative research method uses three different data collection techniques to obtain a more complete picture of the situation. The research location is in the Tanjung Sari sub-district, Natar sub-district, South Lampung. The results showed that the implementation of character education management in developing students' interests, attitudes and positive behavior was based on planning objectively with clear and specific goals, having regular education programs, developing activities in the form of intra-curricular, extracurricular, guidance and counseling program activities with the aim of as the formation of student character education, improving student skills in humanizing practices and other skills. Determination of character education management in developing students' interests, attitudes and positive behavior in the form of long-term and short-term programs carried out by example, direction, assignments, habituation, and the creation of an environment. This affects the character of students in the form of leadership, discipline, trustworthiness, sincerity and decency. These conditions support the creation of an environment that is a healthy and conducive learning environment, everything that is heard, seen, and suggested by students is an element of education.